2017
DOI: 10.1149/2.0301708jss
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Structure of Ceramic Thin Films Deposited by Spray Pyrolysis

Abstract: The method of Spray Pyrolysis (SP) was applied to prepare thin films of ceramic or ceramic-metal (cermets) composites based on Cu starting from aqueous solutions of soluble metal salts. Specifically, air pressurized spray pyrolysis was used in order to prepare thin film cermets of Cu-CeO2, Cu-La0.75Sr0.25Cr0.5Mn0.5O3-δ (Cu-LSCM) and the perovskite La0.75Sr0.25MnO3 (LSM) onto dense and porous YSZ substrates. These films have the potential for application in ceramic fuel cells, ceramic membranes, batteries, cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…LSM and CGO). Dense YSZ substrates were either fabricated or obtained from NEYCO (France) [4]. LSF70 pellets were synthesized from the corresponding powders (prepared also from the respective metal nitrates by a co-precipitation method) and sintered at 1250°C in air for 6h to a final density of 92% of the theoretical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LSM and CGO). Dense YSZ substrates were either fabricated or obtained from NEYCO (France) [4]. LSF70 pellets were synthesized from the corresponding powders (prepared also from the respective metal nitrates by a co-precipitation method) and sintered at 1250°C in air for 6h to a final density of 92% of the theoretical.…”
Section: Methodsmentioning
confidence: 99%
“…In the solution spray pyrolysis (SSP) technique [4], molecular precursors of the desired film are sprayed via a solution onto the substrate held at certain temperature. In principle, salt precipitation, decomposition and subsequent sintering of the formed oxides are combined into one process.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental apparatus used for the spray pyrolysis deposition experiments has been described in detail in previous communications 12,13 and is shown in Figure 1. The system basically consists of a syringe pump which controls the solution flow rate during spraying and an air compressor (vol.50L) with manometer and flow controller which controls the air flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication, 12 we have used the technique of SAT for fabricating films of cermets of the type Cu-CeO 2 , Cu-La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-δ (Cu-LSCM) and the single phase perovskite La 0.75 Sr 0.25 MnO 3 (LSM) onto dense and porous YSZ substrates, identifying the substrate deposition temperature and precursor solution concentration as being the most significant factors that affect film morphology, adhesion and thickness. Moreover, Krestou et al 13 identified an effect of the type of precursor salt in addition to the above parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation